ANALISA RISIKO MSDS DENGAN METODE NORDIC BODY MAP TERHADAP PEKERJA PROYEK CV. MAKARYA ENGINEERING - Muhammad Irfan Rahmadani; muhammad Syahrul Ramadhan; Muhammad Nizar Mahabbi Rosul; Ratna Ayu Ratriwardhani,S.ST., M.T (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
CV. Makarya Engineering is a supervisory consultant in building construction work at SDN Tembok Dukuh II Surabaya, the project work involves a lot of heavy work activities, such as lifting materials, bending while doing work, and other activities that cause complaints of pain in several parts of the body. The Nordic Body Map method is an assessment to find out the body complaints of a person or worker. The Nordic Body Map method uses a 4 Likert scale rating. Workers are interviewed, then give an assessment that has been determined with a Likert scale on the part of the body that feels pain during building construction work activities. Keywords: Musculosketal disorders, Nordic Body Map,building construction project